A procedure to assess disbond growth and determine fatigue life of bonded joints and patch repairs for primary airframe structures. (August 2020) - Tanulia, Veldyanto; Wang, John; Pearce, Garth M.; Baker, Alan; David, Matthew; Prusty, B. Gangadhara
Highlights: Slow growth design strategy for bonded patch repairs, consistent with FAA guidance. A novel specimen configuration to identify the entire disbond crack growth process. The slow growth management approach is applicable for damage in intolerable zone. Fatigue life prediction and inspection interval determination. Significant reduction of maintenance cost potentially from this research. Abstract: This paper assesses the suitability of a damage slow growth management strategy to bonded joints or patch repairs of primary aircraft structures. The entire process of a disbond crack growth from initiation to the ultimate failure of a typical double lap metallic joint is investigated. The residual static strength of the joint as function of disbond crack length is established using the finite element method with adhesive element failure criteria and a progressive failure analysis. For a joint having sufficient static strength safety margin under a typical fatigue loading that would propagate disbond crack, a finite element fracture mechanics analysis indicates that the disbond growth would be stable in a significant length range of the disbond crack, initiated from either "disbond tolerant zone" or "safe-life zone". The analysis further suggests that for local (part width) disbond, due to load redistribution effect the disbond growth rate would be reduced as the disbond propagates. These results suggest the slow growth approach would indeed be feasible. With the above analyses, the framework to implement the slow growth approach, predict allowable fatigue life and determine inspection interval, in accordance with the guidance provided in FAA AC 20-107B [1], is established. Furthermore, this study assesses the effect of rigidity imbalance between inner adherend and outer adherend and shows how varying the adherend thickness could affect the adhesive bond strength and disbond growth rate. This information would be useful in design of validation experiment.